Mineralogy of Nickel and Cobalt Minerals in Xiarihamu Nickel–Cobalt Deposit, East Kunlun Orogen, China - Han, Yixiao; Liu, Yunhua; Li, Wenyuan (Frontiers in Earth Science, 2020)
Located in the East Kunlun Orogen, China, the Xiarihamu magmatic nickel–cobalt sulfide deposit is the country’s second-largest deposit of this type. It was formed in special early Paleozoic with low copper grade (0.14 wt. %) compared with other deposits in same type. The mineralogy of nickel and cobalt minerals, which are direct carriers of these elements, can clearly reflect their behavior in the process of mineralization; however, such information for this deposit remains unreported. In the present study, we use an electron microscope and electron probe micro analyzer to delineate and analyse many nickel and cobalt minerals such as maucherite, nickeline, cobaltite, violarite, gersdorffite, parkerite and arsenohauchecornite in various rocks and ores. With the increase of crustal material contamination, it can reach arsenide saturation locally in sulfide melt, then a separate Ni-rich arsenide (bismuth) melt exsolve somewhere. This melt will crystallize into nickeline, parkerite, arsenohauchecornite and maucherite firstly. Secondly, most of nickel and cobalt tend to enter cobaltite and pentlandite, rather than exist in chalcopyrite and pyrrhotite as isomorphism during sufficient fractional crystallization of sulfide melt, which gathered nickel and cobalt elements widely. Also, more than one magmatism might result in the superposition of ore-forming elements. Later the ore-forming elements redistribute limitedly in hydrothermal process. Not only the metallogenic mechanism model of nickel and cobalt established in the present study explains the process of nickel–cobalt mineralization in Xiarihamu, but also can be applied to similar deposits and has a wide universal replicability.